Evidence for coronavirus discontinuous transcription. - Jeong, Y S (1994)
Coronavirus subgenomic mRNA possesses a 5'-end leader sequence which is derived from the 5' end of genomic RNA and is linked to the mRNA body sequence. This study examined whether coronavirus transcription involves a discontinuous transcription step; the possibility that a leader sequence from mouse hepatitis virus (MHV) genomic RNA could be used for MHV subgenomic defective interfering (DI) RNA transcription was examined. This was tested by using helper viruses and DI RNAs that were easily distinguishable. MHV JHM variant JHM(2), which synthesizes a subgenomic mRNA encoding the HE gene, and variant JHM(3-9), which does not synthesize this mRNA, were used. An MHV DI RNA, DI(J3-9), was constructed to contain a JHM(3-9)-derived leader sequence and an inserted intergenic region derived from the region preceding the MHV JHM HE gene. DI(J3-9) replicated efficiently in JHM(2)- or JHM(3-9)-infected cells, whereas synthesis of subgenomic DI RNAs was observed only in JHM(2)-infected cells. Sequence analyses demonstrated that the 5' regions of both helper virus genomic RNAs and genomic DI RNAs maintained their original sequences in DI RNA-replicating cells, indicating that the genomic leader sequences derived from JHM(2) functioned for subgenomic DI RNA transcription. Replication and transcription of DI(J3-9) were observed in cells infected with an MHV A59 strain whose leader sequence was similar to that of JHM(2), except for one nucleotide substitution within the leader sequence. The 5' region of the helper virus genomic RNA and that of the DI RNA were the same as their original structures in virus-infected cells, and the leader sequence of DI(J3-9) subgenomic DI RNA contained the MHV A59-derived leader sequence. The leader sequence of subgenomic DI RNA was derived from that of helper virus; therefore, the genomic leader sequence had a trans-acting property indicative of a discontinuous step in coronavirus transcription.